Solitary Encapsulated Neurofibroma Not Associated with Neurofibromatosis-1 Affecting Tongue in a 73-Year-Old Female - Sk. Abdul Mahmud; Neha Shah; Moumita Chattaraj; Swagata Gayen (Hindawi Limited, 2016)
Neurofibromas are benign tumors of nerve cell origin arising due to proliferation of Schwann cells and fibroblasts. They are usually asymptomatic and hence remain undiagnosed. They are commonly found on the skin and intraorally tongue is the most common site for their occurrence. Here, we present a unique case of solitary encapsulated neurofibroma in the oral cavity without any clinical manifestations or family history of Neurofibromatosis type 1 in a 73-year-old female patient who presented with a painless swelling on the tongue. The histopathologic findings closely mimicked benign fibrous histiocytoma. In our case, definitive diagnosis of neurofibroma was made based on clinical findings, family history, and histopathological and immunohistochemical evaluation. Through this case report we want to emphasize the role of biopsy and immunohistochemistry in arriving at a confirmatory diagnosis. The patient was treated by surgical excision and showed no signs of recurrence over a follow-up period of 12 months.